The Ambiguous Migrant: From the Book of Ruth Toward a Theology of Migration - Devina Widiningsih; Robert Setio (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2026)
The book of Ruth has long been interpreted as a story of loyalty, divine providence, and the inclusion of the foreigner into Israel. Yet beneath its pastoral surface lies a profound and productive ambiguity that has often been neglected in the history of its interpretation. This paper argues that Ruth the Moabitess embodies an irreducible ambiguity that challenges both nativist and liberal pieties about migration. Drawing on literary analysis, performance criticism, postcolonial theory (particularly Homi Bhabha’s concepts of hybridity, third space, mimicry, ambivalence, and unhomeliness), and a review of classic, feminist, and theological commentaries, we demonstrate that closure readings—whether theological, proselytizing, royal-apologetic, or feminist—domesticate the text’s subversive potential. By recovering Ruth’s ambiguity, this paper constructs a theology of migration that refuses easy answers, embraces liminality as revelation, and locates divine presence precisely in the spaces between certainty and resolution. The result is a situated, dialogical, performative, and hybrid theology that reimagines the migrant not as a problem to be solved but as a gift to be received.